Characterization and Quenching of Autofluorescence in Piglet Testis Tissue and Cells. (30th August 2012) - Yang, Yanfei; Honaramooz, Ali
Abstract : Significant intrinsic fluorescence in tissues and in disassociated cells can interfere with fluorescence identification of target cells. The objectives of the present study were (1) to examine an intrinsic fluorescence we observed in both the piglet testis tissue and cells and (2) to test an effective method to block the autofluorescence. We observed that a number of granules within the testis interstitial cells were inherently fluorescent, detectable using epifluorescence microscopy, confocal laser scanning microscopy, and flow cytometry. The emission wavelength of the autofluorescent substance ranged from 425 to 700 nm, a range sufficiently broad that could potentially interfere with fluorescence techniques. When we treated the samples with Sudan Black B for different incubation times, the intrinsic fluorescence was completely masked after treatment for 10–15 min of the testis tissue sections or for 8 min of the testis cells, without compromising specific fluorescence labeling of gonocytes with lectin Dolichos biflorus agglutinin (DBA). We speculate that the lipofuscin or lipofuscin-like pigments within Leydig cell granules were mainly responsible for the observed intrinsic fluorescence in piglet testes. The method described in the present study can facilitate the identification and characterization of piglet gonocytes using fluorescence microscopy.